2009
DOI: 10.1016/j.dnarep.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Polk mutant mice have a spontaneous mutator phenotype

Abstract: Mice defective in the Polk gene (which encodes DNA polymerase kappa) are viable and do not manifest obvious phenotypes. The present studies document a spontaneous mutator phenotype in Polk−/− mice. The initial indication of enhanced spontaneous mutations in these mice came from the serendipitous observation of a postulated founder mutation that manifested in multiple disease states among a cohort of mice comprising all three possible Polk genotypes. Polk−/− and isogenic wild type controls carrying a reporter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 41 publications
(56 reference statements)
4
58
0
Order By: Relevance
“…An increase in spontaneous mutations in Polk KO mice at 9 months and 12 months of age has been reported [34,35]. Base substitutions of G:C to T:A or G:C to C:G in liver and kidney, and G:C to A:T in lung are probably increased by intrinsic bulky DNA adducts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An increase in spontaneous mutations in Polk KO mice at 9 months and 12 months of age has been reported [34,35]. Base substitutions of G:C to T:A or G:C to C:G in liver and kidney, and G:C to A:T in lung are probably increased by intrinsic bulky DNA adducts.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to TLS, Polk is reported to be involved in nucleotide excision repair [30], replication checkpoint [31], repair of single-strand breaks in DNA [32], and microsatellite stability [33]. Knockout (KO) mice of Polk are viable and exhibit more frequent spontaneous mutations in liver, lung, and kidney in aged mice [34,35]. However, it is still unclear which of the DNA lesions Polk protects cells from in vivo (the whole body system) and what roles it plays in preventing cancer induced by environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with in vitro analyses, Polκ-deficient mouse embryonic fibroblasts (MEFs) and embryo stem cells are sensitive to killing by BP and exhibit increased BPDEinduced mutagenesis (11)(12)(13)(14). E. coli DinB can also correctly incorporate dCMP opposite some N 2 -dG adducts, including N 2 -furfuryl-dG (15) and N 2 -(1-carboxyethyl)-2′-dG (16) with greater catalytic proficiency than opposite normal dG.…”
mentioning
confidence: 78%
“…It was previously shown that Polκ-deficient MEFs are abnormally sensitive to UV radiation (38,39) and BPDE treatments (13,14), and complementation with GFP-Polκ can rescue cellular hypersensitivity. We thus determined whether Polκ-deficient MEFs complemented with WT, PGM1, or PGM2 GFP fusion proteins showed altered sensitivity to BPDE treatment.…”
Section: Steady-state Kinetic Measurements Of Full-length Wt and Mutantmentioning
confidence: 99%
“…Burr et al measured spontaneous mutation rates at two expanded simple tandem repeat (ESTR) loci and reported that the spontaneous mutation rate of Polk 2/2 mice (129Sv*C57BL/6*BALB/c background) was higher than the wild-type Polk 1/1 mice. Stancel et al used the lambda-phage cII mutagenesis assay to determine that Polk 2/2 mice had elevated spontaneous mutagenesis in the kidney, liver, and lung [Stancel et al, 2009]. No defects in somatic hypermutation were reported in Pol j-null mice [Shimizu et al, 2003].…”
Section: Dna Polymerase Kappa (Pol J)mentioning
confidence: 99%